The conceptual framework of moral intensity moderating effect on the relationship between accounting students’ attitude forward community services and soft skills - Xiaoxiao, Jia; Muhamad, Haslinah; Tze, San Ong; Mat Daud, Zaidi; Mingyue, Chu (Asian Scholars Network, 2022)
Cases of accounting fraud emerge one after another in companies around the world. Although listed companies are required to disclose accurate and transparent financial statements in time, and these financial statements are audited by certified public accountants, it is still difficult to avoid the occurrence of accounting fraud. The purpose of this study is to study the stage of accountants' learning moral education in universities on the basis of the original corporate governance. Based on the experiential learning theory, this paper offers the conceptual framework regarding the moderating effect of moral intensity in the relationship Between Accounting students' attitude forward community services and soft skills. The lab uses questionnaires to collect data on students' attitudes, soft skills and moral strength toward community service. Data collected to validate students' attitudes toward community service can improve their soft skills, and this relationship will be further consolidated under the positive regulation of moral strength.